Characteristics and spatial identification of Antillean manatee (Trichechus manatus manatus Sirenia: Trichechidae) strandings in Guatemala - Machuca-Coronado, Oscar (2023)
Introduction: Marine mammal strandings can be used to determine the impacts of anthropogenic activity on the species survival, population health, and levels of environmental pollution in ecosystems. In addition, these data can help design conservation and management strategies as well as identify priority areas for the species. The West Indian manatee (Trichechus manatus) is listed as endangered throughout its range. In Guatemala, it is distributed along the Caribbean coast. Anthropogenic activities appear to be having a direct pressure on the species, affecting the status of the population. Objective: The general purpose of this study was to analyze the 30 years of documented manatee stranding reports available for Guatemala. Two specific objectives were defined to: 1) conduct a spatial analysis of manatee strandings to identify the areas of high stranding concentration, and 2) determine whether there were sex differences in the number of strandings. Methods: Characteristics and areas of concentration of manatee strandings were described along the Caribbean coast between 1992 to 2022. Sites with the highest probable density of strandings were identified using a Kernel density analysis. We compared the number of stranding events that occurred in each protected area that included manatees in their management plans and each municipality of Izabal. We determined whether there were sex differences in the number of stranded manatees. We use the potential biological removal to estimate the maximum number of manatees that can be removed from the population due to anthropogenic causes without negatively impacting species survival. Results: Forty-three manatee stranding events were recorded throughout the species’ range in Guatemala (48 total individuals). The sites with the highest predicted density of strandings were Santo Tomás de Castilla bay, followed by Lake Izabal (including the limits of the Refugio de Vida Silvestre Bocas del Polochic) and Parque Nacional Río Dulce. The majority of the cases were registered in protected areas (60 %). Estimates of potential biological removal were equivalent to less than one manatee per year, which was exceeded by the annual average of stranded manatees recorded (three manatees). Conclusions: Anthropogenic activities cause mortality of manatees in this region, despite the implementation of protected areas. Poaching was identified as the main cause of manatee mortality in Guatemala. The implementation of management strategies focused on minimizing threats to the species, based on the application of environmental legislation and environmental awareness, is essential. The creation and implementation of a protocol for the stranding of marine mammals on the Caribbean coast of Guatemala is necessary, in order to obtain standardized records of these events and conduct rescue efforts and releases when possible.